274 Thrombotic complications in patients with COVID-19 requiring hospitalisation: a single centre prospective service evaluation. Issue 12 (23rd November 2020) - Habeichi, Wadhi; Bell, Jack; Khawaja, Zohaib; Exley, Joshua; Horner, Daniel
Abstract : Aims/Objectives/Background: Early experience of the coronavirus pandemic has led to concerns regarding hypercoaguability and increased rates of venous thromboembolic (VTE) disease. As a result, many centres have changed front door thromboprophylaxis risk assessment and prescribing practice. There is no clear evidence that such new approaches are safe, or improve patient outcomes. We sought to establish the incidence of thrombotic complications in all hospitalised patients with confirmed COVID-19, at a UK thrombosis exemplar centre. Methods/Design: A single site prospective service evaluation (Ref: S20HIP17). We identified all patients with COVID-19 who were hospitalised between 1st March and the 31st May 2020, encompassing the UK acceleration, peak and deceleration phases of the pandemic. Standard risk assessment and weight adjusted pharmacological thromboprophylaxis were conducted in accordance with previous national and local guidelines. We report follow up data as of the 1st July (minimum 4 weeks post diagnosis), using an established method for national VTE reporting metrics. Results/Conclusions: A total of 528 hospitalised patients had confirmed COVID-19 during the study period, of which 74 (14.0%) were admitted to critical care. Mean age was 69.6 (SD 16.7) and the median duration of admission 7 days (IQR 16). Mortality was 35.6%. We identified 12 VTE positive episodes at follow up, including 9 pulmonary emboli (PE) and 3 deep vein thromboses (DVT). Over 60% of PE events were isolated segmental or subsegmental thrombi, suggestive of 'immunothrombosis' in situ and of questionable clinical significance. VTE event rates for our population were 2.3% overall and 6.8% for those admitted to critical care. Rates of VTE did not appear to differ from pre-pandemic levels (figure 1 ). We did not find increased rates of clinically significant VTE events in hospitalised patients with COVID-19. Our findings raise questions regarding the merits of unvalidated risk assessment tools and increased thromboprophylaxis dosing strategies in COVID-19 patients.